2011
DOI: 10.1021/tx200080b
|View full text |Cite
|
Sign up to set email alerts
|

Cytochromes P450 Catalyze the Reduction of α,β-Unsaturated Aldehydes

Abstract: The metabolism of α,β-unsaturated aldehydes, e.g. 4-hydroxynonenal, involves oxidation to carboxylic acids, reduction to alcohols, and glutathionylation to eventually form mercapturide conjugates. Recently we demonstrated that P450s can oxidize aldehydes to carboxylic acids, a reaction previously thought to involve aldehyde dehydrogenase. When recombinant cytochrome P450 3A4 was incubated with 4-hydroxynonenal, O2, and NADPH, several products were produced, including 1,4-dihydroxynonene (DHN), 4-hydroxy-2-none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…Similar to the results presented here, CYP2C29 mRNA has been shown to be mainly expressed in liver and lung but also in many other organs (Choudhary et al, 2003). CYP2C29 detoxifies a-and b-unsaturated aldehydes, found endogenously in food and in the environment, which can otherwise react with genomic material (Amunom et al, 2011). Our data identified CYP2B9 as the most abundant murine P450 in brain, and sexually dimorphic expression was not observed.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the results presented here, CYP2C29 mRNA has been shown to be mainly expressed in liver and lung but also in many other organs (Choudhary et al, 2003). CYP2C29 detoxifies a-and b-unsaturated aldehydes, found endogenously in food and in the environment, which can otherwise react with genomic material (Amunom et al, 2011). Our data identified CYP2B9 as the most abundant murine P450 in brain, and sexually dimorphic expression was not observed.…”
Section: Discussionsupporting
confidence: 88%
“…The major metabolic route involves oxidation to cinnamic acid, b-oxidation, and conjugation of the acid metabolites. Aldehyde dehydrogenase has been suggested as the enzyme responsible for the conversion to cinnamic acid (Bickers et al, 2005), but there are also many examples of P450-mediated metabolism of aldehydes (Raner et al, 1996;Amunom et al, 2007Amunom et al, , 2011Kaspera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, earlier studies showed both oxidative and reductive metabolism of 4-HNE in human keratinocytes, as well as the formation of GSH reaction products (Aldini et al , 2003; Aldini et al , 2007). A number of enzymes have been identified that metabolize 4-HNE, including alcohol dehydrogenase, aldehyde dehydrogenase, aldo-keto reductases, cytochrome P450's and glutathione S-transferases (Hartley et al , 1995; Srivastava et al , 2000; Amunom et al , 2011). Glutathione S-transferases conjugate 4-HNE to glutathione, a process that promotes its extracellular transport (Tjalkens et al , 1999).…”
Section: Discussionmentioning
confidence: 99%